The Use of 5-Aminosalicylic Acid in Children and Adolescents With Inflammatory Bowel Disease. Issue 10 (November 2018) - Sokollik, Christiane; Fournier, Nicolas; Rizzuti, David; Braegger, Christian P.; Nydegger, Andreas; Schibli, Susanne; Spalinger, Johannes
Abstract : Background: In ulcerative colitis (UC) 5-aminosalicylic acid (5-ASA) is recommended as primary therapy for mild to moderate disease. Topical 5-ASA has been proven especially effective. In Crohn's disease (CD) the evidence for a beneficial role of 5-ASA is weak. We investigated the use of topical and systemic 5-ASA therapy in children and adolescents with inflammatory bowel disease. Materials and Methods: Data of patients younger than 18 years, registered between April 2008 and December 2015 in the Swiss Inflammatory Bowel Disease Cohort, were analyzed. Results: Three hundred twenty pediatric inflammatory bowel disease patients were included; 189 with CD and 131 with UC. Over one third of UC patients [51 (39%)] received topical 5-ASA therapy and 43 (33%) received combination therapy during their disease course. UC patients with left-sided colitis or proctitis were more likely to receive topical or combination therapy as compared with patients with pancolitis ( P <0.001 and <0.001, respectively). An increase in the use of topical 5-ASA therapy in UC patients was noted over time from 5% to 38%. Forty-seven percent of CD patients were treated with oral 5-ASA during their disease course. The usage was stable over time at approximately 15% to 20%. Conclusions: In recent years a very positive trend showing an increase in topical 5-ASA therapy in children and adolescents with UC has been observed. However topical therapy is still used with relative low frequency, especially in patients with a more extensive disease. Conversely, despite weak evidence supporting 5-ASA use in CD patients it has been frequently prescribed. Physicians should continue to encourage their UC patients to use topical therapy.